Information and Technology Governance Capability Analysis: Case Study of CV Wirelessindo - Reihan Putra Oktavio; Achmad Nizar Hidayanto (Jurnal Indonesia Sosial Teknologi, 2024)
The implementation of information and technology (IT) supports company sustainability. Large companies use IT as an integral part of their business model. Digital strategies must align with business strategies to achieve sustainability. Wirelessindo, established in 2007, provides IT solutions such as equipment, site surveys, network design and security, and tower installations. Its mission is to increase company productivity to win the competition in the era of Industry 4.0. It is used to enhance customer service and internal business process efficiency. Initial investigations found issues with IT function mismatches, financial losses due to data loss, IT equipment installation and configuration errors, and business process incidents caused by emerging risks. Identified root problems include employee knowledge gaps, risk management disparities, errors in defining business needs, and change management gaps. Based on these findings, IT governance eval_uation was chosen as the research focus. This study aims to provide an overview of CV Wirelessindo IT capability levels and recommend improvements to meet expected levels. A mixed-method approach and COBIT 2019 were used in this study. The General Manager, IT Division Manager, Software Development Team, Network Monitoring Team, Project Manager, and HR Manager were selected as respondents based on the RACI chart guidelines. Of the nine selected objectives, BAI08 showed level 0. APO12, BAI02, BAI06, BAI07, and DSS01 showed level 1. APO07, BAI10, and DSS03 showed capability level 2. Therefore, 61 recommendations were provided to raise the IT governance capability level to level 3 for all objectives.